2003
DOI: 10.1021/la035519y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Microtubule Guiding on Microfabricated Kinesin-Coated Surfaces:  Chemical and Topographic Surface Patterns

Abstract: Cells regulate active transport of intracellular cargo using motor proteins. Recent nanobiotechnology efforts aim to adapt motor proteins to power the movement and assembly of synthetic materials. A motor-protein-based nanoscale transport system (molecular shuttle) requires that the motion of the shuttles be guided along tracks. This study investigates the principles by which microtubules, serving as shuttle units, are guided along micrometer-scale kinesin-coated chemical and topographical tracks, where the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(194 citation statements)
references
References 34 publications
8
181
5
Order By: Relevance
“…A number of groups have shown that three dimensional patterns on motor-coated surfaces will bend or buckle microtubules and reorient their direction (Hiratsuka et al, 2001;Hess et al, 2002;Clemmens et al, 2003;Moorjani et al, 2003;van den Heuvel et al, 2005). However, because the channels are open on their top, detachment from the surface prevents complete redirection and requires an influx of new microtubules to compensate for microtubules lost from the surface.…”
Section: Enclosed Microchannels Redirect Moving Microtubulesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of groups have shown that three dimensional patterns on motor-coated surfaces will bend or buckle microtubules and reorient their direction (Hiratsuka et al, 2001;Hess et al, 2002;Clemmens et al, 2003;Moorjani et al, 2003;van den Heuvel et al, 2005). However, because the channels are open on their top, detachment from the surface prevents complete redirection and requires an influx of new microtubules to compensate for microtubules lost from the surface.…”
Section: Enclosed Microchannels Redirect Moving Microtubulesmentioning
confidence: 99%
“…A number of groups have shown that microfabricated surface features such as walls and channels can be used to redirect and control the trajectory of kinesin-driven microtubules (Hiratsuka et al, 2001;Hess et al, 2002;Clemmens et al, 2003;Moorjani et al, 2003). However, in most of these demonstrations the top of the channels are open to the bulk solution and because filaments can detach from the kinesin coated surface and diffuse away, microtubules are lost from the surface over time (half of the observed population in some designs (Clemmens et al, 2004;van den Heuvel et al, 2005)).…”
Section: Introductionmentioning
confidence: 99%
“…[35] More recent studies have demonstrated the confinement of microtubules in micro-channels fabricated in kinesin-adhesive PU and AZ5214 photoresist. [60,111] Mechanical-only confinement within deep channels and walls with retrograde slopes has been successful for microtubules [60] but less likely for small and very flexible actin filaments, [112] although the retrograde slope should in principle be effective.…”
Section: Lateral Confinement Of Movement Formentioning
confidence: 99%
“…Therefore this method allowed us to limit the kinesin-driven movement of microtubules effectively to one dimension along a linear track. The sidewall collisions described above and the subsequent guidance of microtubules along the sidewall were well characterized by [49]. Similar nano-structured surfaces were also used for the actomyosin system [40] although actin filaments often climbed up the wall and escaped from tracks owing to their lower flexural rigidity compared with microtubules.…”
Section: Controlling the Direction Of Protein Filament Movement Usingmentioning
confidence: 99%
“…Given the potential applications of this system, it is thus necessary to develop a way to restrict the movement of filaments to one dimension along linear tracks for extended periods of time. Restricting kinesin-driven movement of microtubules along linear tracks was achieved by using micrometer-scaled grooves lithographically fabricated on glass surfaces [48][49][50]. In the presence of detergent, kinesin selectively adsorbed onto a glass surface from which the photoresist polymer has been removed, not on the photoresist polymer itself [50].…”
Section: Controlling the Direction Of Protein Filament Movement Usingmentioning
confidence: 99%